Proceedings of the 18th International Conference on Environmental Degradation of Materials in Nuclear Power Systems - Water Reactors - Jackson, John H.; Paraventi, Denise; Wright, Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This two-volume set represents a collection of papers presented at the 18th International Conference on Environmental Degradation of Materials in Nuclear Power Systems - Water Reactors. The purpose of this conference series is to foster an exchange of ideas about problems and their remedies in water-cooled nuclear power plants of today and the future. Contributions cover problems facing nickel-based alloys, stainless steels, pressure vessel and piping steels, zirconium alloys, and other alloys in water environments of relevance. Components covered include pressure boundary components, reactor vessels and internals, steam generators, fuel cladding, irradiated components, fuel storage containers, and balance of plant components and systems.
Special Topics II - Processes -- Investigation Of Pitting Corrosion In Sensitized Modified High-Nitrogen 316LN Steel After Neutron Irradiation -- Quantifying Erosion-corrosion Impacts on Light Water Reactor Piping -- Effect of Molybdate Anion Addition on Repassivation of Corroding Crevice in Austenitic Stainless Steel -- Effect of pH on Hydrogen Pick-up and Corrosion in Zircaloy-4 -- Oxidation Kinetics of Austenitic Stainless Steels as SCWR Fuel Cladding Candidate Materials in Supercritical Water -- A Recent Look at CANDU Feeder Cracking: High Resolution Transmission Electron Microscopy and Electron Energy Loss near Edge Structure (ELNES) -- Part 13. Cables and Concrete Aging and Degradation - Cables -- Simultaneous Thermal and Gamma Radiation Aging of Electrical Cable Polymers -- Principal Component Analysis (PCA) as a Statistical Toolfor Identifying Key Indicators of Nuclear Power Plant Cable Insulation Degradation -- How Can Material Characterization Support Cable Aging Management? -- Aqueous Degradation in Harvested Medium Voltage Cables in Nuclear Power Plants -- Frequency Domain Reflectometry Modeling and Measurement for Nondestructive Evaluation of Nuclear Power Plant Cables -- Aging Mechanisms and Nondestructive Aging Indicator of Filled Cross-linked Polyethylene (XLPE) Exposed to Simultaneous Thermal and Gamma Radiation -- Successful Detection of Insulation Degradation in Cables by Frequency Domain Reflectometry -- Capacitive Nondestructive Evaluation of Aged Cross-Linked Polyethylene (XLPE) Cable Insulation Material -- C-2: Tracking of Nuclear Cable Insulation Polymer Structural Changes using the Gel Fraction and Uptake Factor Method -- C-4: Degradation of Silicone Rubber Analyzed by Instrumental Analyses and Dielectric Spectroscop.
Keywords: Materials -- Analysis; Nuclear engineering; Characterization and Analytical Technique; Nuclear Energy